Identifikasi Tumbuhan Berkhasiat Obat Tradisional Berbasis Pengetahuan Lokal Di Desa Hepang Kecamatan Lela Kabupaten Sikka - Yosefina Orance; Yulimira Syafriati Y. M. Sani; Dian Ernaningsih (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to explore the potential of plant species used in traditional medicine, the organ parts used and the processing of medicinal plants. This research was conducted for 2 weeks from March 14 to March 27, 2023 in Hepang Village. This study uses a type of science research with identification and exploration survey methods. The population of this study amounted to 15 people consisting of Battra (Traditional Medicine) 3 people, 6 patients and 6 people in general. Based on the results of the study found 22 types of medicinal plants namely Peperomia pellucida, Euphorbia thymifolia, Piper batle, Euphorbia hirta, Momodirca charantia, Curcuma domestica, Choromolaena odorata, Orthosiphon stamineus, Morinda citrifolia, Paederia foetida, Kaemferia galanga, Morus alba, Sonchus arvensis, Anomianthus dulcis, Gynura procumbens, Centella asiatica, Phyllanthus niruri, Androrapis paniculata Ness, Pluchea indica, Alstonia scholaris, Physalis angulata, Elephantopus scaber, which consists of 14 families, the most widely used Asteraceae. The most widely used organ parts are leaves 53%, roots 26%, rhizomes 7%, while the least used organs are stems, fruits and sap 3%. The processing is very traditional, namely by boiling, pounding, squeezing, squeezing, chewing, soaking, grinding and cutting.